Robert Spaemann’s Critique of Counterrevolutionary Political Theology - Jokubaitis, Linas (Politologija, 2024)
The aim of the article is to prove that Robert Spaemann’s interpretations of the inversion of teleology, Bonald’s political theology and nihilism of the right can be applied in a critical analysis of Carl Schmitt’s decisionistic counterrevolutionary political theology. Schmitt formed his theoretical positions by developing the insights of the doctrines of Thomas Hobbes and Catholic counterrevolutionary political theorists. Spaemann’s analysis shows that the author of Leviathan presented a political theory based on the inversion of teleology in which self-preservation was understood as the highest aim of politics. Bonald’s political theology radicalizes the Hobbesian tradition, the necessity to preserve social order at any price becomes the absolute goal of politics. In a functionalistic ontology of nihilistic right which is based on the inversion of teleology, Christian belief is functionalised, it becomes a tool which is used in attempts to secure the preservation of society. Spaemann’s critical interpretation of political nihilism shows that Schmitt’s political theology can be understood as a reaction to the nihilism of the left, however, it asserts the position of the nihilism of the right in which the aim of the state is understood by absolutising the principle of in suo esse perseverare.